DANGDORA KOVI: SIKLUS KEHIDUPAN WANITA DAYAK SOPUNTAN DALAM KARYA TARI - Sisilia Hangin (Joged, 2020)
Karya berjudul “Dangdora Kovi” adalah video tari yang bersumber dari ritual upacara adat yang dilakukan wanita suku Dayak Soputan dalam siklus kehidupan yaitu lahir, tumbuh, dan dewasa. Tradisi dalam suku Dayak Soputan merupakan suatu kebiasaan yang dilakukan dalam setiap peristiwa ataupun proses kehidupan, yang mengandung nilai, makna, serta tujuan tertentu. Gerak tari berangkat dari pola tradisi dengan pengembangan motif gerak nyerilit, seliung, ngancet, dan kepupeq yang dirangkum ke dalam tiga segmen. Pola iringan menggunakan instrumen Sapeq dan Gong, dan hutan dipilih sebagai tempat pementasan karya. Sinematografi adalah sebuah ilmu terapan yang membahas tentang penangkapan gambar dan sekaligus penggabungan gambar tersebut, sehingga menjadi rangkaian gambar yang memiliki kemampuan menyampaikan ide dan cerita, yang dilengkapi dengan konsep Ten Tools, menjadi teknik yang digunakan untuk menciptakan panggung baru dalam seni pertunjukan tari dengan penggunaan kamera untuk mengarahkan presepsi penonton terhadap visual yang dilihat. ABSTRACTTradition in the Dayak Soputan tribe is a custom carried out in every event or process of community life, that iscontains certain values, meanings, and goals. The dance work entitled "Dangdora Kovi "comes from the life process of Dayak Soputan women in their tradition, The stylists link the life processes of Dayak women in their tradition to customs dangdora, above becomes a sequence that is applied into the structure a single dance work entitled Dangdora Kovi, by applying management traditional ceremonial rituals, personal experiences, and ideas of dance stylists with forms movements which are summarized into dance videos. The presentation of the work "Dangdora Kovi" departs from the traditional pattern with development of motive motion nyerilit, seliung, ngancet and kepupeq. This work presented the ceremonial procession, personal experiences, and ideas of the stylists which is summarized into three segments, namely birth, growth and adulthood. This work carrying midi music (recording), using Sapeq and Gong as basic instruments of dance music. The forest is the selected place as the background staging works. Cinematography is an applied science that discusses capture images and at the same time combining these images, so that it becomes a series of images that have the ability to convey ideas and stories, equipped with the concept of Ten Tools, the technique used for creating a new stage in the performing arts of dance with use a camera to direct the audience's perception of the visuals they see.